The Routledge companion to talent management - Tarique, Ibraiz (Business & Management, 2022)
The field of Talent Management has grown and advanced exponentially over the past several years as organizations, large and small, public and private, global and domestic, have realized that to gain and sustain a global competitive advantage, they must manage their talents effectively. Talent Management has become a major theoretical and empirical topic of intellectual curiosity from various disciplinary perspectives, such as human resource management, arts and entertainment management, international management, etc. This Companion is an indispensable source that provides an authoritative, in-depth, and comprehensive examination of emerging Talent Management topics. Divided into five thematic sections that provide a unique overarching structure to organize forty-one chapters written by leading and renowned international scholars, this Companion assesses essential knowledge, trends, debates, and avenues for future research in a single volume: Evolution and Conceptualization of Talent Management; The External Context of Talent Management; The Internal Context of Talent Management; Individuals, Workforce, and Processes of Talent Management; and Outcomes of Talent Management. In this way, the Companion is essential reading for anyone involved in the scholarly study of Talent Management, including academic researchers, advanced postgraduate and graduate students, and management consultants. For further debate on Talent Management, readers might be interested in the supplementary volume Contemporary Talent Management: A Research Companion, sold separately